Probability of nucleation events and aerosol particle concentration in different air mass types arriving at Hyytiälä, southern Finland, based on back trajectories analysis - Sogacheva, L.; Dal Maso, M.; Kerminen, V.-M.; Kulmala, M. (Boreal Environment Research Publishing Board, 2024)
The probability of a new ultrafine particle formation as well as the spatial sources of the nucleation, Aitken and accumulation modes of particles measured in Hyytiälä, southern Finland, were investigated using air mass history analysis. The studied period covered the years 1997–2003. We estimated the probability of a new ultrafine particle formation for nine sub-areas inside a domain limited by 50°N–80°N in latitude and 30°W–60°E in longitude. For all the seasons North Atlantic and arctic regions dominated as an origin of air masses that accompany nucleation events. The probability of nucleation events in Hyytiälä reached its maximum in spring and summer with north and north-west air masses transfer directions. The highest concentration of nucleation mode particles was observed in arctic and polar air masses, whereas the highest concentration of accumulation mode particles was observed during intrusions of continental air masses.